EDUKASI PENYULUHAN OBAT DAN PENGOBATAN GRATIS BAGI MASYARAKAT DI DESA PERKAMPUNGAN ADAT SIJUNJUNG - Dwisari Dillasamola; Yoneta Srangenge; Aan Ardiansyah; Yufri Aldi; Fatma Sri Wahyuni; Elidahanum Husni; Rahmad Abdillah; Adinny Julmiza; Benardo Benardo (BULETIN ILMIAH NAGARI MEMBANGUN, 2024)
Community health education is crucial, including education on the rational use of antibiotics, as well as halal food and medicine. Additionally, providing free medical treatment has a significant impact, encouraging the community to prioritize health and maintain it as a primary concern. This community service project was conducted in the Desa Perkampungan Adat Sijunjung. The objective of this activity is to maintain and improve the community's health status. One way to achieve this is through community service activities. The service involved educational sessions on medicines and health, as well as free medical treatment, in collaboration with the Faculty of Pharmacy and the Faculty of Medicine at Universitas Andalas. The education targeted pregnant women and the elderly, focusing on proper medication selection, rational use of antibiotics, and education on halal medicines and food. Free medical treatment involved specialist doctors and pharmacists, who also provided counseling on medications to patients. The results of the activity showed high community enthusiasm, with more than 100 prescriptions filled. The education on the rational use of medications, particularly antibiotics, is expected to increase community awareness and knowledge. This activity also highlights the importance of pharmacists in providing patient-oriented pharmaceutical services, as well as the importance of promotional and preventive efforts in maintaining public health. It can be concluded that free medical treatment is expected to encourage the community to be more health-conscious and less fearful of seeking medical care.